THE BRAVERY OF MARTHA IN KNIVES OUT MOVIE DIRECTED BY RIAN JOHNSON - Pangestu, Maulani; Pratiwi, Elvira Lestari; Buansari, Istihayyu (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
The purpose of research is to find out about the bravery needed in life in daily life. This research was carried out through a film titled Knives Out which was released in 2019, Directed by Rian Johnson. The author wants to analyze the causes of braveness. The writer chose Knives Out movie and used the main character as the object of this research. This research method is a qualitative descriptive method. The results of this study are: (1) The main character's braveness is based on Rahman's theory: Decision-Making and Impulsivity, Risk-Taking Behavior and Sensation Seeking, Self-Confidence and Altruism (2) Actions of main character’s braveness: Confess Her Fault, Finding the Truth, Fight for Her Rights, Proving the Truth. Brave is one of the many important qualities that we must possess. The importance of the presence of people around you, just to remind you of the wrong decision that will be taken. Instead of regretting later, it's better to listen to the opinion of the people closest to be considered in making decisions.